The effects of perceived teacher support and growth language mindset on learner well-being in AI-integrated environment: the mediating role of generative AI attitude - Pan, Yong; Li, Gengchun (Frontiers in Psychology, 2025)
IntroductionWith continuing advancements in AI technologies, the landscape of English as a foreign language (EFL) teaching and second language acquisition (SLA) is undergoing transformative changes, with learners' emotions in AI-integrated environments capturing more and more research attention. However, a dearth of studies has paid attention to learner well-being in such environments and its influencing factors.MethodsBased on previous research on perceived teacher support (PTS) and growth language mindset (GLM) in EFL educational contexts, the present study explored the possible direct effects of PTS and GLM and the mediating effect of generative AI attitude on learner well-being among a sample of Chinese university EFL learners (N = 486), using a questionnaire survey, and utilizing statistical procedures such as correlation analysis, regression analysis, and mediation analysis.ResultsThe results indicated that: (1) both PTS and GLM significantly and positively predicted generative AI attitude and learner wellbeing; (2) generative AI attitude significantly and positively predicted learner well-being; and (3) generative AI attitude played a partial and positive mediating role in the relationships between PTS/GLM and learner wellbeing.DiscussionThe research findings are expected to provide practical insights into fostering university EFL learners' well-being in AI-integrated environments.